Anatomy, taxonomy and phylogeny of the Eocene guitarfishes from the Bolca Lagerstätten, Italy, provide new insights into the relationships of the Rhinopristiformes (Elasmobranchii: Batomorphii). Issue 4 (11th December 2020) - Marramà, Giuseppe; Carnevale, Giorgio; Naylor, Gavin J P; Varese, Massimo; Giusberti, Luca; Kriwet, Jürgen
Abstract: We here re-evaluate the skeletal anatomy and the systematic position of the two Eocene guitarfish species represented by almost complete and articulated material from the Konservat-Lagerstätten of Bolca in Italy. The analyses of morphometric, skeletal and dental features of ' Rhinobatos ' dezignii and ' R. ' primaevus allow them to be excluded from the living guitarfish genus Rhinobatos and assigned to the new genera † Pseudorhinobatos gen. nov. and † Eorhinobatos gen. nov., respectively. The placement of these new genera within the rhinopristiform family Rhinobatidae is based on the possession of a series of morphological features (e.g. pectoral fins fused to head forming a wedge-shaped pectoral disc; rostral cartilage extending to the tip of the snout; nuchal cartilages and horn-like processes of nasal capsules absent; teeth with Rhinobatos -like morphology displaying smooth enameloid, central uvula and two lateral uvulae) that unambiguously exclude their assignment to any other rhinopristiform family. A new morphology-based phylogenetic analysis that includes the two new fossil genera, described herein, provides novel insights into the relationships of the Batoidea and recovers the Rhinopristiformes as a paraphyletic group. This indicates that the monophyly of extant taxa could be the result of the extinction of crucial taxa.